FIRST LOCALITY RECORD OF JAVAN ENDEMIC DAMSELFLY DREPANOSTICTA GAZELLA LIEFTINCK, 1929 (ODONATA: ZYGOPTERA: PLATYSTICTIDAE) IN EAST JAVA, INDONESIA - Shahroni, Abdul Mutholib; Rahma, Nabila (ZOO INDONESIA, 2023)
Drepanosticta gazella has been reported only to spread on Java Island, Indonesia, to be exact, in the western and central parts. An accidental encounter with a male D. gazella occurred in the tropical rainforest of the highlands of Mount Penanggungan, Mojokerto, East Java, on vegetation near a small stream. This record represents the easternmost area within the distribution range of this endemic species. In addition, further exploration in East Java at several important locations needs to be carried out in order to determine the expansion of its distribution. Keywords: Distribution, Drepanosticta, Java, odonata, range expansion